CARA MELIHAT - Prasetyo, Andry (Acintya, 2019)
Abstract This study discusses John Berger's book entitled: The Way of Seeing which was first printed in 1972. The purpose of this study is to urge photographers to study harder and implement critical theories about concepts and philosophies that support photography. This language urgency helps foster the critical spirit and instinct of students who are studying photography.This research departs from a literature review. Because of its basic research, with qualitative descriptive forms, it is in the search for data sources on primary and secondary data. Primary data is Berger's original work entitled How to Look, while the secondary one is a review and commentary on Berger's main work by other authors.The results of this study show the concept of thought of John Berger: Seeing the building of our existence in the world that surrounds us, therefore we can explain in words, whatever is around us. Seeing not only the affairs of the mechanical reaction of the eye organs (lens, retina, etc.) but there is the activity of choosing from so many things outside us that are visible to the eye. Keywords: John Berger, How to Look, Critical Theory, Photographer